Mastering orthopedic techniques intra-articular fractures - Malhotra, Rajesh (Jaypee, 2013)
Mastering Orthopedic Techniques series, this comprehensive manual is a complete guide to the surgical management of intra-articular fractures. Beginning with an introduction providing an overview of articular fractures, the following chapters provide a 'how to' style commentary, joint by joint and by fracture type.